Recycling of used vegetable oils by powder adsorption - Mannu, Alberto (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2023)
The treatment of used vegetable oil (UVO) with seven different adsorbents and through two different procedures (stirring and gravity filtration) was explored. Important differences in terms of density, turbidity, electrical resistance, free fatty acids (FFAs) content and relative fatty acid distribution were observed. Different outcomes were shown depending both on the adsorbent and on the procedure. Lower values of density and FFAs were registered for oils treated by gravity filtration with portland (respectively 0.6% and 0.81 g/ml) and celite (respectively 0.7% and 0.72 g/ml). Considering the undesired leaching from the powder to the oil, related to the turbidity, the celite resulted more suitable for the oil recycling (241 Nephelometric Turbidity Unit (NTU) for portland vs 184 NTU for celite). In addition, Fourier-transform infrared spectroscopy combined with multivariate analysis allowed to determine a chemical fingerprint relative characteristic of vegetable oils recycled by gravity or by adsorption by stirring